ANTIHYPERCHOLESTEROLEMIC EFFECT OF Arcangelisia flava STEM EXTRACT IN HYPERLIPIDEMIC RATS - Evi Umayah Ulfa; Ema Rachmawati (UNEJ e-Proceeding)
Cardiovascular diseases especially coronary heartdisease (CHD) is the main disease cause death in theworld. The mortality rate of CHD (26.4%) is higherthan the mortality rate of cancer (6%). IndonesianHealth Department in 2002 reported that one offour people were died due to CHD. Hyperlipidemia isa major risk factor for CHD. Hyperlipidemia is lipidmetabolism disorder characterized by an elevationof total cholesterol (TC), triglyceride and low densitylipoprotein (LDL) cholesterol 1.Arcangelisia flava Merr is a plant belongs toMenispesmaceae family, comonly known as yellowroot. A flava is Indonesian medicinal plant that havebeen used traditionally for malaria, diabetes mellitus(DM), urinary stones, jaundice, diarrhea and skinabscess 2,3,4.The water extract of A. flava showedantimicrobial activity5. Methanolic extract of A. flavahas antioxidant and cytotoxic effect against brineshrimps and breast cancer cells (MCF-7)4. The Ethylacetate fraction of A. flava have been proven toreduce blood sugar level of diabetic rats6. The majorchemical compounds of stem of A. flava is alkaloidincluding berberine, palmatine, jathorrizine andcolumbamime7. Flavonoid, saponin, tanin andfuranoditerpene are other compounds of A. flava8.Berberine isolated from Coptis sinensis can decreasetotal cholesterol and triglycerides by increasingexpression of the hepatic low density lipoproteinreceptor (LDLR)9.Our previous study showed that methanol extract ofleaf of A. flava reduced TC and LDL cholesterol.These extract was capable to decrease theatherogenic index value and the number of foamcells10,11. Antihyperlipidemic effect of A flava wascaused by berberine and flavonoid in the extract.The berberine content of stem was higher than leafof A. flava12. In order to know the antihyperlipidemiceffect of stem extract of A. flava, the influence ofmethanolic extract of A. flava stems (EMBAf) ontotal cholesterol, triglyceride, LDL cholesterol andHigh Density Lipoprotein (HDL) cholesterol levels hasbeen determined in hyperlipidemic induced rats.